Morphological and wear behavior of low temperature thermochemical gaseous nitriding process - Paijan, Lailatul Harina; Maleque, Md. Abdul (MYTRIBOS, 2022)
In this study, the nitride layer based on incorporation of nitrogen diffusion via low temperature thermochemical nitriding process were prepared. Nitriding temperature, holding time and gas flow rate during nitriding process was used as the parameters to assess morphology and wear behavior. Nitriding holding time was varies for 4, 8 and 12 hours, meanwhile temperature and glass flow rate were keep constant. The thickness and hardness of nitride layer varied with the holding time with the thickest layer of 60.5 µm and surface hardness of 513.3 HV0.5. The nitride layers, containing expanded austenite, Fe3N and CrN phases, as well as solid solution in the stainless steel were developed during low temperature thermochemical gas nitriding process. The expanded austenite formation on the nitride layers demonstrates that the best wear behavior due to the highest hardness. The wear rate and CoF improved by 0.40 and 0.37 compared to untreated DSS, respectively. Furthermore, it was revealed that the worn surface showed very mild striation of wear for the 12 hours compared to 4 hours nitrided sample which demonstrated deeper grooves on the shorter nitriding process. It was demonstrated that nitriding process is capable and feasible to produce hard surface layer on DSS with higher hardness and wear resistance properties which can be used for tribological applications.